Effect of participation in development initiatives on competitive advantages, performance, and sustainability of micro-enterprises in Malaysia - Abdullah Al Mamun; Rajennd Muniady; Noorul Azwin Binti Md Nasir (Contemporary Economics, 2021)
This study assessed the impact of micro-enterprise development initiatives (commonly provide access to financial services and micro-enterprise development training programs to low-income households) upon competitive advantages, performance, and sustainability of micro-enterprises owned and managed by selected low-income households in Peninsular Malaysia. Upon the adoption of cross-sectional design, data were randomly gathered from 300 micro-entrepreneurs residing in four states of Peninsular Malaysia selected from the eKasih database (national poverty data bank). The quantitative data had been collected by holding structured interview sessions with the participants from October until November 2017. The study outcomes revealed that the total amount of economic loan received, the total number of training hours and the number of center meetings/discussion attended exerted significantly positive effects upon competitive advantage, while marital status (control variable) was found to affect competitive advantage in a significantly positive manner. As for micro-enterprise performance, length of participation and number of center meetings/discussions attended as well as marital status as the control variable exhibited significantly positive effects. Meanwhile, the impact of participation duration, total amount of economic loan received, and number of center meetings/discussions attended upon micro-enterprise sustainability seemed to be inconclusive. Additionally, age of entrepreneurs and duration of enterprises establishment (micro-enterprise established) appeared to affect the aspect of sustainability. The findings appear to emphasize on the mixed effects of participation in development initiatives on competitive advantage, performance, and sustainability of micro-enterprises. Hence, this study recommends that the government of Malaysia formulate and adopt more specific strategies and policies in advocating development initiatives to ensure positive progression amongst micro-entrepreneurs and micro-enterprise owners.
Keywords: F61; M21; 330; Development Initiatives; Competitive Advantages; Performance; Sustainability